A lifing method based on R5 and viscoplasticity modelling and its application to turbine rotor under thermomechanical loading. (March 2020) - Bonetti, R.; Hadjipakkos, P.; Rae, Y.; Hughes, J.; Sun, W.
Highlights: An integrated life assessment framework for structures under thermomechanical loadings is proposed. The framework is based on R5 and viscoplasticity modelling. The procedure is implemented on an industrial gas turbine. Abstract: An integrated life assessment procedure for structures operating under thermomechanical loading has been developed. The methodology uses a viscoplasticity based framework combined with the R5 life assessment code. The viscoplastic constitutive model used for the stress-strain analysis is derived from the Chaboche-Lemaitre formulation that allows to directly obtain the required parameters for the R5 assessment as stress relaxation per cycle and the elastic follow-up factor. The R5 procedure is therefore significantly simplified. The proposed life assessment procedure is demonstrated on a martensitic steel (FV566) industrial gas turbine rotor under a typical start up – shut down operation. The effect of creep-fatigue interaction at different locations within the rotor structure is assessed and the remaining life at each location is calculated. A sensitivity study is performed at half load, which shows an increase in lifetime of the rotor.